2013
DOI: 10.1111/j.1742-9544.2012.00091.x
|View full text |Cite
|
Sign up to set email alerts
|

The Moderating Effects of Mindfulness on Psychological Distress and Emotional Eating Behaviour

Abstract: Current evidence and theory suggests that emotional eating resulting from attempts to manage psychological distress, such as anxiety, depression, and stress, is considered to be a major contributor to obesity. Mindfulness has been shown to be related to disordered eating behaviours. Employing a non-clinical sample of 42 males and 115 females, the present study investigated the contribution of mindfulness as a potential moderator between psychological distress and engagement in emotional eating, while controlli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
39
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 56 publications
(47 citation statements)
references
References 54 publications
7
39
1
Order By: Relevance
“…These findings are consistent with previous studies in non-clinical samples (Lattimore et al, 2011;Masuda et al, 2012;Pidgeon et al, 2013). In addition, it was found that dispositional mindfulness was associated with more restrained eating behaviour.…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…These findings are consistent with previous studies in non-clinical samples (Lattimore et al, 2011;Masuda et al, 2012;Pidgeon et al, 2013). In addition, it was found that dispositional mindfulness was associated with more restrained eating behaviour.…”
Section: Discussionsupporting
confidence: 94%
“…In addition, heightened awareness of one's internal states, including hunger, satiety and affect, as a result of mindfulness (Baer et al, 2006;Kristeller & Wolever, 2011) should, theoretically, decrease emotional and external eating (Van Strien et al, 1986). Indeed, in student samples, dispositional mindfulness has been associated with greater awareness of healthy dietary habits and less emotional eating (Pidgeon, Lacota, & Champion, 2013); less emotional and uncontrolled eating (Lattimore, Fisher, & Malinowski, 2011); less disordered eating (Masuda, Price, & Latzman, 2012); and fewer bulimic symptoms (Lavender, Jardin, & Anderson, 2009). Recently, also in a sample of bariatric surgery patients, dispositional mindfulness was associated with less emotional and external eating behaviour (Ouwens, Schiffer, Visser, Raeijmaekers, & Nyklíček, 2014).…”
Section: Introductionmentioning
confidence: 93%
“…Intuitive eating was associated with a lower BMI in four studies (68,70,74,75) . Other observations included a decreased emotional eating with higher levels of mindfulness (76,77,79) and a higher level of everyday mindfulness was related negatively to self-report serve size of energy-dense food (83) . In one of…”
Section: Summary Of Results From Observational Studiesmentioning
confidence: 99%
“…Nutrition Research Reviews (68,70,74,75) Mindful eating and decreased BMI 1 Positive (82) Intuitive eating and blood markers of cardiovascular risk 1 Positive (70) Mindfulness and decreased portion size 1 Positive (83) Intuitive eating and observing hunger cues 1 Positive (72) Mindfulness and decreased binge eating 2 Positive (76,80) Mindfulness and decreased emotional eating 3 Positive (76,77,79) Mindfulness and external eating 1 Positive (77) Mindfulness and reduced cravings 1 Positive (78) Mindfulness and restrained eating 1 Positive (75) Intuitive eating and freedom to eat 1 Positive (73) Intuitive eating and interoceptive sensitivity 1 Positive (71) Trait mindfulness and returning baseline brain network post-food cue exposure 1 Positive (78) Mindful eating and mental well-being 1 Positive (81) Intuitive eating and more pleasure associated with food 1 Positive (75) Intuitive eating and increased external and introjection regulation in behaviour questionnaire 1 Positive (69) * Note that effect size is not accounted for in the coding of positive. The code only provides an indicator of direction of results and is not trying to assess overall evidence.…”
Section: Summary Of Results From Observational Studiesmentioning
confidence: 99%
See 1 more Smart Citation